Giant perigenital seborrheic keratosis - Debabrata Bandyopadhyay; Abanti Saha; Vivek Mishra (Wolters Kluwer Medknow Publications, 2015)
Seborrheic keratosis (SK) is a very common benign epidermal proliferation that is prevalent in all races. Most commonly occurring on the trunk, face, scalp, and the extremities, they can occur anywhere on the body except the palms and soles. The most common appearance is that of a very superficial verrucous plaque which appears to be stuck on the surface. Giant lesions are very rare, and their location on the genital area is rarer still. We report here a case of multiple giant SK lesions in a 59-year-old man.